A route-creating algorithm for Saildrones by comparing a pseudo straight-line route and wind direction (LACCEI, 2024)
Control algorithms for drones are commonly focused on transporting the robot from point A to point B, this type of straight route becomes sufficient in the case of aerial drones, but in the case of a Saildrone (Marine drone propelled partially or totally by a sail, commonly rigid), A straight navigation between 2 points is not optimal. That is why navigation strategies are used for the control of vehicles with sail, consisting of the variation of the angle of attack of the sail and the route that the vehicle will follow. This last parameter of the strategy is the one that is sought to be obtained through an algorithm based on obtaining the real-time coordinates of the drone and the dest ino, together with the direction of the wind and the inclination of the Saildrone with respect to magnetic North, joining all these data through analytical geometry equations in order to be implemented in an autonomous drone controlled by a Raspberry SBC Pi 4. In this way it is sought that the routes generated are similar to those commonly used in sailboat navigation, with the ability to update the route in case the initial parameters vary unexpectedly, whether the location of the planeor the direction of the wind, in order to obtain an energy saving greater than 50% with respect to following a route in a straight line.